Research of the Ability to Define Practical Problems - Lazarev V.S; Nosova L.N (Moscow State University of Psychology and Education, 2020)
The article presents a study of one of the most important qualities of the subject of activity, the ability to define practical problems. The purpose of the study is to find answers to two questions: what determines the ability of a person to define problems and how can we promote the development of this ability? The research hypothesis is based on L.S. Vygotsky's theory of sign mediation of mental functions and of the mechanisms of psychological development, as well as on V.V. Davydov's activity theory of thinking and its development. The hypothesis of the study is that, firstly, the differences in the operational structure of the action of problem-setting and its performance are determined by whether it is mediated by the empirical or theoretical concept of the problem; secondly, it is possible to develop the ability to define problems through specially organized training which ensures the activity-based acquisition of the cultural methods of problem-setting. We developed a training program and a test for assessing an individual's ability to define problems. The experiment was conducted on the basis of the Surgut State Pedagogical University and involved 61 third-year students: 31 in the experimental group (30 females and 1 male) and 30 in the control one (all females). The study shows that, depending on the nature of mediation of the action of the problem, its operational structure and performance differ qualitatively. Besides, it is possible to qualitatively improve the ability of the person to define problems through the implementation of the activity-based training program.